Pathogenic nature of Syncephalastrum in Atta sexdens rubropilosa fungus gardens - Barcoto, Mariana O [UNESP]; Pedrosa, Felipe [UNESP]; Bueno, Odair C [UNESP]; Rodrigues, Andre [UNESP] (Wiley, 2017)
BACKGROUND: Leaf-cutter ants are considered to be a major herbivore and agricultural pest in the Neotropics. They are often controlled by environmentally persistent insecticides. Biological control using pathogenic fungi is regarded as an alternative for the management of these insects. Here, we assess whether the filamentous fungus Syncephalastrum sp. is a pathogenic microorganism responsible for a characteristic disease in fungus gardens. We also characterise the damage caused by this fungus by evaluating physiological and behavioural responses of Atta sexdens rubropilosa subcolonies infected with Syncephalastrum sp. RESULTS
Keywords: biological control; co-infection; inhibition; interaction; leaf-cutter ants; opportunistic fungi; sulfluramid